48 Accessing Respite Services for People with Dementia and Their Carers: A Qualitative Study with Multiple Stakeholders. (16th September 2019) - O'Shea, Emma; Timmons, Suzanne; O'Shea, Eamon; Irving, Kate
Abstract: Background: People with dementia and carers do not always access respite services in a timely manner, and in some cases, they do not access respite services at all. While carers' perspectives on respite access have been explored, other stakeholder perspectives, especially those of people with dementia, are under-represented in the existing literature. The aim of this study was to synthesise multiple stakeholders' perspectives, including people with dementia, on accessing respite services. Methods: Purposive sampling was employed. Semi-structured interviews were conducted with 35 key stakeholders, including people with dementia (N=6), carers (N=9), respite front-line staff (N= 4), respite managers (N=8), primary care professionals (N=3) and policy-makers/academics (N=5). Informed consent was obtained from all stakeholders who could give this. Dewing's 'process consent' method was employed in relation to people with dementia. Data were interpreted inductively using thematic analysis. We aimed to move beyond the semantic level of meaning, and to interpret patterns of meaning in the data. Reflexivity was considered throughout the research process. Results: Three themes ('Service Acceptability'; 'Navigational Knowledge and Skills'; 'Constructing and Adjudicating Respite Need') were identified that relate to how access to respite services is negotiated between service providers and dyads. Conclusion: A number of the findings support previous research; however novel findings discussed relating to the access negotiation process include 1) the ambiguous legitimacy of respite needs, in a system configured to deliver a biomedical model of care and which considers non-medical care as a family responsibility, and 2) the constraining effects of disparate conceptualisations of 'respite' between carers and providers. Future research should interrogate the appropriate boundaries of public responsibility in relation to respite service planning/delivery for dementia, with particular reference to client preferences for community and in-home provision.